PRIMARY CEREBRAL VASCULITIS AS CAUSE OF ISCHEMIC STROKE - CASE REPORT - Aleksovska, Angela; Stomnaroska, Daniela Ristikj; Veljanovski, Dimitar; Zikova, Sanja Dzambazovska; Cangovska, Tatjana Cepreganova; Lickova, Elena (Journal of Morphological Sciences, 2024)
Primary vasculitis of the central nervous system (PACNS) is a rare disorder of the blood vessels of the brain and the spinal cord without any evidence of systemic vasculitis. The clinical course of cerebral vasculitis ranges from fulminant to indolent and may be marked by fluctuations in clinical signs. We present the case of a 45 years old male patient who was admitted to our hospital due to exhibiting symptoms consistent with a frontal lobe syndrome. Clinically, he manifested alterations in behavior, apathy, and loss of sphincter control. The initial symptoms he had one month prior to the admission to our hospital were left hemiparesis, confusion and disorientation. Onset at a young age and absence of risk factors indicated the presence of an uncommon cause of stroke. To elucidate the underlying cause, a series of examinations were conducted, including three instances of brain MRI scans, computed tomography angiography, carotid Doppler ultrasound, and an electroencephalogram.The finding of morphologically altered blood vessels, with thickening of the wall of the right internal carotid artery, with reduced and irregular flow, reduced flow speeds and initial vascular resistance along the entire length up to the intracranial entrance does not rule out that it can be one of the forms of vasculitis. Key words : vasculitis,angiitis, stroke, brain,magnetic resonance imaging.